Research of Ceramic Matrix for a Safe Immobilization of Radioactive Sludge Waste; AIP Conference Proceedings; Vol. 1938 : Isotopes: Technologies, Materials and Application (ITMA-2017) - Dorofeeva (Dorofeyeva) L. I. Liudmila Ivanovna (2018, 2018)
Title screen